Glucose and fructose hydrogel enhances running performance, exogenous carbohydrate oxidation, andgGastrointestinal tolerance - Rowe, J. T.; King, R. F.; King, A. J.; Morrison, D. J.; Preston, T.; Wilson, O. J.; O'hara, J. P. (Medicine & Science in Sports & Exercise, 2022)
Purpose Beneficial effects of carbohydrate (CHO) ingestion on exogenous CHO oxidation and endurance performance require a well-functioning gastrointestinal (GI) tract. However, GI complaints are common during endurance running. This study investigated the effect of a CHO solution-containing sodium alginate and pectin (hydrogel) on endurance running performance, exogenous and endogenous CHO oxidation, and GI symptoms.